2021
DOI: 10.1071/mf20303
|View full text |Cite
|
Sign up to set email alerts
|

The more the merrier: using environmental flows to improve floodplain vegetation condition

Abstract: Environmental flows are increasingly being used to restore degraded floodplain vegetation; however, the type of flow regime required for recovery to healthy condition can vary depending on the extent of degradation before restoration. Regulation of the River Murray has affected floodplain ecosystems at many locations, including Bottle Bend Reserve, in south-western New South Wales, Australia. Within Bottle Bend Reserve, tangled lignum (Duma florulenta) dominates sections of the higher floodplain elevations. Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Floodplains are a significant feature of riverine landscapes; current estimates suggest floodplains occupy >3.14 × 10 6 km 2 of the global land surface (Tockner and Stanford, 2002;Thoms and Parsons, 2016), yet Frontiers in Environmental Science frontiersin.org efforts to understand floodplain environmental flows and their functional responses to environmental watering is limited. Environmental flows are increasingly being used to restore degraded floodplain vegetation; however, the type of flow regime required for recovery to healthy conditions has varied because of limited knowledge of the interactions between flow, floodplain topography, the state of vegetation, and vegetation responses to flow variability (Campbell et al, 2021). This case study of the Yanga Floodplain, Australia, highlights the importance of floodplain geomorphology, and specifically, the importance of the complexity of the floodplain surface in providing the template upon which the diversity of ecosystem responses is set.…”
Section: Functional Flows In the Floodplainmentioning
confidence: 99%
“…Floodplains are a significant feature of riverine landscapes; current estimates suggest floodplains occupy >3.14 × 10 6 km 2 of the global land surface (Tockner and Stanford, 2002;Thoms and Parsons, 2016), yet Frontiers in Environmental Science frontiersin.org efforts to understand floodplain environmental flows and their functional responses to environmental watering is limited. Environmental flows are increasingly being used to restore degraded floodplain vegetation; however, the type of flow regime required for recovery to healthy conditions has varied because of limited knowledge of the interactions between flow, floodplain topography, the state of vegetation, and vegetation responses to flow variability (Campbell et al, 2021). This case study of the Yanga Floodplain, Australia, highlights the importance of floodplain geomorphology, and specifically, the importance of the complexity of the floodplain surface in providing the template upon which the diversity of ecosystem responses is set.…”
Section: Functional Flows In the Floodplainmentioning
confidence: 99%
“…In recent years, climate change and human activities (such as dam construction) have significantly altered the natural characteristics of floodplain floods, leading to the degradation of floodplain ecosystems in irreversible ways [9][10][11][12]. Current research on ecological restoration in floodplain areas primarily focuses on enhancing the hydraulic connectivity of surface water (SW) through floodplain floods [13][14][15][16][17][18][19]. However, it is imperative to adopt a comprehensive water resource management perspective and prioritize an in-depth exploration of the transformation relationship between floodplain floods and GW.…”
Section: Introductionmentioning
confidence: 99%
“…Li, Gong, et al (2019) classified land cover to calculate the ecological water storage of the marsh in the beginning, middle and late stage of plant growth. Campbell et al (2021) surveyed the floodplain vegetation condition over 1 year to determine the e‐flows, and demonstrated the value of increased flow frequency in recovering vegetation health. Gong et al (2021) assessed the area change of reed marshes and the instantaneous evapotranspiration of the wetland, and found that the distribution of evapotranspiration within a year presented single‐peak curve and the water replenishment should be changed according to seasons.…”
Section: Introductionmentioning
confidence: 99%